Incidence of complete agenesis of dorsal wall of sacral canal: study of dry human sacra - Pandey, Mritunjay (International Journal of Research in Medical Sciences, 2020)
Background: The human sacrum is a large, triangular shield-shaped bone formed by the fusion of five separate vertebrae along with the inter-vertebral discs. Gross morphology of sacrum shows a concave ventral surface, a convex dorsal surface and a triangular sacral canal. The sacral canal consists of an anterior wall formed by the fusion of the posterior aspect of the bodies of sacral vertebrae and the dorsal wall is formed by the fused laminae, spines and ossified ligamentum flava. Spina bifida is a developmental defect of sacral vertebrae, where the dorsal wall of sacral canal is partially or completely absent. The present study is an attempt to verify the incidence of complete agenesis of dorsal wall of sacral canal. Methods: Eighty six dry human sacra were collected from the undergraduate students and department of anatomy of three different medical colleges of Uttar Pradesh for the study of dorsal wall of sacral canal. Results: Out of eighty six bones studied, two (2.33%) of the bones showed complete absence of the dorsal wall of the sacral canal. Conclusions: Complete agenesis of dorsal wall of sacral canal may lead to partial or complete failure of caudal epidural anaesthesia. Association between dorsal sacral agenesis and some other congenital malformations have also been reported by few authors. Anatomical knowledge of these variations of dorsal wall of sacral canal is important for anaesthetists, radiologists and spine surgeons.